Pomacea canaliculata (Lamarck, 1828) as bioindicator of the presence of cadmium in the rivers Guayas, Daule and Babahoyo (Revista Científica Ciencias Naturales y Ambientales, 2016)
The Guayas river basin is the largest of Ecuador, it is formed by the confluence of the Daule and Babahoyo rivers. Previous studies demonstrate that they are exposed to direct discharge of wastewater and chemicals used in agricultural practices. Thereby, concentrations of cadmium (Cd) in water and sediment that might be bioacumulate for the apple snail (Pomacea canaliculata) have been recorded. Cadmium is a cosmopolitan pollutant that causes a great environmental impact, assuming carcinogenics effects to the human. The aim of this work is verify if Pomacea canaliculata is a bioindicator of the presence of Cd in the Guayas, Daule and Babahoyo rivers, for this purpose concentrations of Cd in water, sediment and Pomacea canaliculata are tested and compared. All samples were carried to dry weight, digested and analyzed for atomic absorption spectrophotometry of flame. Pearson`s correlation and Principal Components Analysis proved a correlation between the bioavailable concentration of Cd in sediment and water (r2=0,768, p=0,000); moreover, Pomacea canaliculata presented a positive correlation when compared to the concentrations of bioavailable Cd in sediment (r2=0,528, p=0,004). Finally, we conclude that Pomacea canaliculata is a reliable bioindicator of the presence of Cd in the aquatic environment.
Keywords: Apple snail; Babahoyo; bioavailability; bioindicator; cadmium; Daule; Guayas; Pomacea canaliculata